“Flypaper effects” in transfers targeted to women: Evidence from BRAC's “Targeting the Ultra Poor” program in Bangladesh - Roy, Shalini; Ara, Jinnat; Das, Narayan Chandra; Quisumbing, Agnes R. (Science Direct, 2022)
This article was published in The Journal of Development Economics [Open access, licensed under CC BY-NC-ND 4.0] and the definite version is available at: https://doi.org/10.1016/j.jdeveco.2015.06.004 The Article's website is at: https://www.sciencedirect.com/science/article/pii/S0304387815000656?via%3Dihub